The History of Carbohydrates in Type I Allergy - Hils, Miriam; Wölbing, Florian; Hilger, Christiane; Fischer, Jörg; Hoffard, Nils; Biedermann, Tilo (Frontiers in Immunology, 2020)
Although first described decades ago, the relevance of carbohydrate specific antibodies as mediators of type I allergy had not been recognised until recently. Previously, allergen specific IgE antibodies binding to carbohydrate epitopes were considered to demonstrate a clinically irrelevant cross-reactivity. However, this changed following the discovery of type I allergies specifically mediated by oligosaccharide structures. Especially the emerging understanding of red meat allergy characterized by IgE directed to the oligosaccharide alpha-gal showed that carbohydrate-mediated reactions can result in life threatening systemic anaphylaxis which in contrast to former assumptions proves a high clinical relevance of some carbohydrate allergens. Within the scope of this review article, we illustrate the historical development of carbohydrate-allergen-research, reaching from only diagnostically relevant crossreactive-carbohydrate-determinants to clinically important antigens mediating type I allergy. Focusing on clinical and immunological features of the alpha-gal syndrome, we highlight the discovery of oligosaccharides as potentially highly immunogenic antigens and mediators of type I allergy, report what is known about the route of sensitisation and the immunological mechanisms involved in sensitisation and elicitation phase of allergic responses as well as currently available diagnostic and therapeutic tools. Finally, we briefly report on carbohydrates being involved in type I allergies different from alpha-gal.